IT-baseret fagleksikografi: nye perspektiver - Laursen, Anne Lise; Duvå, Grete (Nordiske Studier i Leksikografi, 2003)
With the new possibilities offered by hypertext versions of different reference works including dictionaries, space is no longer a matter of concern in relation to the design of the dictionary itself, which means that there is an indefinite variety of ways to present lexical information. The aspect of efficiency in the use of the dictionary or reference work is an important factor for the translator and therefore we want to discuss how the lexicographer can profit from the dynamism and the flexibility of cyberspace to make a new design of the LSP dictionary. We propose a dictionary which no longer has only one target group but several target groups with different levels of knowledge. Thus, the user can select and chose exactly the information, he or she needs in a given situation. The user can design his own version of the dictionary.